Elder Abuse : Research, Practice and Policy - Dong, XinQi (Springer International Publishing : Imprint: Springer, 2017)
This book provides a global comprehensive and systematic state-of-the review of this field that fills the gaps between research, practice, and policy. The book addresses the epidemiology of the issue and the global prevalence of elder abuse in both developed and developing countries, which synthesizes the most up-to-date data about risk factors and protective factors associated with elder abuse and consequences of elder abuse; clinical assessment and management of elder abuse, including screening, detection, management of elder abuse, and the role of decision making capacity and forensic approaches; practice and services that describe adult protective services, legal justice, elder court systems, and guardianship system; elder abuse and culture, which provides more in-depth anthropological and ethnographic experiences; policy issues, which highlights the elder justice movement, GAO reports, elder justice act, older American act and elder justice coordinating council; and future directions, which explores translational research, practice, education/training and policy issues surrounding elder abuse. Elder Abuse: Research, Practice and Policy is a useful resource for aging researchers, social services, general internists, family medicine physicians, social workers, nurses, and legal professionals interested in the issues of elder abuse.
Keywords: Medicine.; General practice (Medicine).; Geriatrics.; Nursing.; Primary care (Medicine).; Medical research.; Quality of life.; elektronické knihy; electronic books